Bayesian analysis of stochastic process models - Rios Insua, David, 1964-; Ruggeri, Fabrizio; Wiper, Michael P. (Chichester, West Sussex : Wiley, 2012)
'This book provides analysis of stochastic processes from a Bayesian perspective with coverage of the main classes of stochastic processing, including modeling, computational, inference, prediction, decision-making and important applied models based on stochastic processes. In offers an introduction of MCMC and other statistical computing machinery that have pushed forward advances in Bayesian methodology. Addressing the growing interest for Bayesian analysis of more complex models, based on stochastic processes, this book aims to unite scattered information into one comprehensive and reliable volume'--
'A unique book on Bayesian analyses of stochastic process based models'--
Includes bibliographical references and index.
Keywords: Bayesian statistical decision theory; Stochastic processes